Isolation and Identification of High-Yield Ethyl Acetate-Producing Yeast from Gujinggong Daqu and Its Fermentation Characteristics. (3rd April 2018) - Fan, Guangsen; Sun, Baoguo; Xu, Dai; Teng, Chao; Fu, Zhilei; Du, Yihua; Li, Xiuting
ABSTRACT: Ethyl acetate is used to judge the style and quality of baijiu. Therefore, it is of significance to improve and strengthen the stability of baijiu quality by improving and controlling the levels of ethyl acetate. The aroma-producing yeasts are the main strains that produce ethyl acetate and have been used to better effect in baijiu production. In this article, a high-yield ethyl acetate-producing yeast strain named Y3604 was isolated from Gujinggong Daqu by screening and ethyl acetate analysis. According to the morphological properties, physiological and biochemical characteristics, and 26S rDNA sequence analysis, strain Y3604 was identified as Wickerhamomyces anomalus . The optimum fermentation conditions of Y3604 for producing ethyl acetate were obtained by single-factor experiments. When W. anomalus Y3604 was inoculated into sorghum hydrolysate medium (SHM) with the addition of 4% anhydrous ethanol and 0.1% acetic acid, fermented at 25°C with a shaking speed of 210 rpm for 96 h, and a 8°Brix medium, the total ethyl acetate production was 16.92 g/L. This strain has the potential to increase the content of ethyl acetate in baijiu production and enhance the aroma characteristics of baijiu. Thus, it has potential application value in improving the quality of baijiu.